On Inextensible flows of curves according to alternative moving frame. Issue 1 (2nd January 2017) - Körpinar, Talat
Abstract: In this paper, we investigate inextensible flows of curves according to alternative moving frame in Euclidean space 𝔼 3 . Using the Prenet frame of the given curve, we present partial differential equations. The concepts with the inextensible flows are analyzed by using alternative moving frame.